A prática de terapeutas ocupacionais na atenção primária à saúde no Brasil - Silva, Rodrigo Alves dos Santos (2020)
BACKGROUND: Research on occupational therapists' practices can increase understanding and clarity about the role of these professionals in Primary Health Care (PHC). GENERAL OBJECTIVE: To identify, describe and analyze the practice of the occupational therapists in PHC in Brazil. METHODOLOGY: The construction of data occurred through mixed methods with the development of an explanatory sequential strategy outlined in two connected phases: Phase 1 - mostly quantitative, contemplated the collection of quantitative and qualitative data through an Internet Surveys; Phase 2 - only qualitative, contemplated a study of Grounded Theory (TFD), in the constructivist perspective. In Phase 1 - an online questionnaire was applied with the participation of 105 occupational therapists from PHC in the country. For the analysis of quantitative data related to the number of practices performed and the profile of the professionals, the chi-square test was applied with a significance level of 5%. Qualitative data were explored through thematic analysis. In Phase 2 - among the 105 occupational therapists participating in Phase 1, eight were selected, which represented the concentration of professionals in Extended Family Health and Primary Care Centers (NASF-AB) in capitals and metropolitan regions in the northeast and southeast. In this Phase 2, the data were constructed through eight intensive interviews and two observations of occupational therapists' practices in NASF-AB. The analysis was outlined by the initial, focused and theoretical coding, in addition to triangulation of qualitative data between phases 1 and 2. Phase 3 - consisted of the analysis, interpretation and discussion of the results, which enabled an analysis of mixed methods. RESULTS: Phase 1 (quantitative results): 60 practices performed by professionals were identified. Statistically significant associations were observed between: - the total number of practices, and the professional being from NASF-AB and indicating interprofessional practices; - the number of individual, family and group practices with the professional being from the NASF-AB; - the number of interprofessional practices with professionals from NASF-AB and from Multiprofessional Residency; - the number of intersectoral practices with the presence of interprofessional practices; - the number of comprehensive practices with postgraduate PHC experience; - the support, disease prevention and health promotion and education practices with the occupational therapist come from the north and northeast regions of the country; - the number of practices in network with health services and the size of the municipality. The essential and derived attributes of PHC obtained high positive scores, as guiding professional practice. Phase 1 (qualitative results): through thematic analysis, three categories were identified: a) Specific practices of occupational therapists who expressed the strategies, the technologies used and their objectives; b) Theoretical and technical guidance of professional practices were expressed in a different way and with little detail; c) Doubts, limits, challenges and strengths of the practices of occupational therapists in PHC. Phase 2 (qualitative results): The central category “Practices in construction: the work process of occupational therapists in PHC” was based on four categories: 1 - Matrix support practices: technical and pedagogical. 2 - Matrix support practices: clinical-care; 3 - Characteristics and basis of professional practice in PHC; 4 - Challenges for the practice of occupational therapists in PHC. DISCUSSION (PHASE 3): The joint interpretation of the results of the mixed methods research allowed us to infer that the broad scope of professional practices in PHC can enhance interprofessional practice, network collaboration and comprehensive PHC. There was also an interface between the essential attributes and derivatives of PHC and occupational therapy practices and that its work process is under construction and consists of specific and shared practices linked to matrix support: technical-pedagogical and clinical-care. FINAL CONSIDERATIONS: It is possible to defend the legitimacy of occupational therapists' practices in PHC in Brazil and affirm that they are carried out in a contextualized way with people, families and communities that present varied health needs and / or specific problems.